2021
DOI: 10.1111/ctr.14407
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion of the donor is associated with stage 3 primary graft dysfunction after lung transplantation

Abstract: Background:The first aim of this study was to assess the association between stage 3 PGD and pre-donation blood transfusion of the donor. The secondary objectives were to assess the epidemiology of donor transfusion and the outcome of LT recipients according to donor transfusion status and massive donor transfusion status.Methods: This was an observational, prospective, single-center study. The results are expressed as absolute numbers, percentages, medians, and interquartile ranges. Statistical analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Furthermore, these complications lead to primary graft dysfunction and recipient mortality. [28–30] We did not investigate the influence of transfusion on recipient prognosis; nonetheless, our findings provided the evidence for justifying the restriction of transfusion at a hemoglobin concentration of 7 g/dL.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, these complications lead to primary graft dysfunction and recipient mortality. [28–30] We did not investigate the influence of transfusion on recipient prognosis; nonetheless, our findings provided the evidence for justifying the restriction of transfusion at a hemoglobin concentration of 7 g/dL.…”
Section: Discussionmentioning
confidence: 92%
“…Perioperative transfusion of allogeneic blood products in both donor [ 21 , 22 , 23 ] and recipient has been widely associated with an increased risk of primary graft dysfunction (PGD) and 1-year mortality [ 24 , 25 , 26 ]. While these studies have highlighted an association between transfusion and poorer outcomes, it is difficult to determine whether the impact of transfusion is related to the nature of the products administered or to the bleeding that led to the transfusion.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike atherosclerosis or sepsis, where both HDL-C concentration and HDL particle functionality have been extensively studied (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), only a few studies have reported HDL-C levels in the context of respiratory disease and LT (26). A retrospective analysis of 126 consecutive individuals evaluated for LT with a diagnosis of COPD showed that HDL-C levels were increased and this was partially attributable to oral steroid use (27).…”
Section: Discussionmentioning
confidence: 99%
“…The selection of lung transplant candidates (16) and perioperative care (17)(18)(19)(20) was standardized for all patients according to current practices. During the intraoperative period, haemodynamic status was monitored using invasive arterial blood pressure, central venous and Swan Ganz catheters, and trans-oesophageal echocardiography.…”
Section: Perioperative Managementmentioning
confidence: 99%